Principles of pharmacogenetics and pharmacogenomics - Altman, Russ B. 205766; Flockhart, David A. 545131; Goldstein, David B. 545132 (Cambridge ; New York : Cambridge University Press, 2012)
"This book is intended to introduce the field of phamacogenetics and pharmacogenomics to health care professionals. It brings together the latest informaiton about how human genetics impacts drug response phenotypes. It is written to enable the reader to undestand the current knowledge and challenges to the field"--Provided by publisher.